“Cash Masters” Coming Out as “Straight”: Social Media and the Changing Dynamics of Gender and Sexuality - Sozen Basturk (Social Media + Society)
This article explores a novel concept called “straight cash master” emerging on social media platforms, especially X. The concept refers to relationships where self-identified straight men act as masters and primarily gay individuals take on the role of slaves. Several factors make this concept worthy of examination. First, these relationships are complex, involving dimensions of financial domination, sexuality, emotionality, and psychology. Second, while elements of sex work, fetishism, and BDSM (Bondage, Discipline, Sadism, and Masochism) culture are present, categorizing these masters solely as sex workers or performers and using a single theoretical framework for analysis may be inadequate. Third, the “straight” identity of these cash masters does not orient them toward the opposite sex but rather involves same-sex interactions. Thus, their “straightness” lacks the opposite sex and can only be articulated if relied on the same-sex slaves, thereby queering the notion of straightness. Finally, while social media perpetuates traditional norms of gender, sexuality, and masculinity, it also enables such relationships to emerge, having a queering effect. Despite its relevance, there is a noticeable gap in the literature addressing the interplay between social media and this concept. Drawing on unstructured, in-depth interview and qualitative content analysis methods, this article represents the first attempt, to the best of the author’s knowledge, to address this gap and offers a queer reading of it.